Epidermal Cells Methods and Protocols - Turksen, Kursad.; Turksen, Kursad. (Methods in Molecular Biology,, 2010)
In recent years, our ability to understand and manipulate epidermal cells has increased tremendously, opening significant new possibilities in both basic science research and in regenerative medicine, including would healing and transplantation. Epidermal Cells: Methods and Protocols, Second Edition expands upon the popular first edition by bringing together a panel of experienced basic and clinical researchers to describe in step-by-step detail the powerful methods they have developed and optimized to analyze and manipulate epidermal cell precursors and mature epidermal cells. These protocols cover different methods and models for culturing epidermal cells, for enriching very early epidermal progenitors, as well as for studying epidermal cell commitment and differentiation both in vitro and in vivo. Topics of special interest include the derivation, characterization, and utility of epidermal stem cells, mature epidermal cells and their characterization, and applications in regenerative medicine. The protocols follow the successful Methods in Molecular Biology™ series format, providing introductions to their respective topics, lists of the necessary materials and reagents, and notes on troubleshooting and avoiding known pitfalls. State-of-the-art and highly practical, Epidermal Cells: Methods and Protocols, Second Edition offers experienced and novice investigators alike an invaluable collection of readily reproducible techniques designed to broaden not only our understanding of the biology of epidermal cells, but also their utility in normal tissue homeostasis and regenerative medicine applications.